Localized task-invariant emotional valence encoding revealed by intracranial recordings. Issue 6 (23rd December 2021) - Weisholtz, Daniel S; Kreiman, Gabriel; Silbersweig, David A; Stern, Emily; Cha, Brannon; Butler, Tracy
Abstract: The ability to distinguish between negative, positive and neutral valence is a key part of emotion perception. Emotional valence has conceptual meaning that supersedes any particular type of stimulus, although it is typically captured experimentally in association with particular tasks. We sought to identify neural encoding for task-invariant emotional valence. We evaluated whether high-gamma responses (HGRs) to visually displayed words conveying emotions could be used to decode emotional valence from HGRs to facial expressions. Intracranial electroencephalography was recorded from 14 individuals while they participated in two tasks, one involving reading words with positive, negative, and neutral valence, and the other involving viewing faces with positive, negative, and neutral facial expressions. Quadratic discriminant analysis was used to identify information in the HGR that differentiates the three emotion conditions. A classifier was trained on the emotional valence labels from one task and was cross-validated on data from the same task (within-task classifier) as well as the other task (between-task classifier). Emotional valence could be decoded in the left medial orbitofrontal cortex and middle temporal gyrus, both using within-task classifiers and between-task classifiers. These observations suggest the presence of task-independent emotional valence information in the signals from these regions.